Effect of Fertilizer With Potassium Humate and the Method of Addition to the Growth and Yield of Red Cabbage: Pengaruh Pupuk Kalium Humate dan Cara Penambahannya terhadap Pertumbuhan dan Hasil Kubis Merah - Noha Waleed Qader; Sahar Ali Khalo (Universitas Muhammadiyah Sidoarjo, 2024)
Background: The application of potassium humate has been recognized for its potential to enhance plant growth and yield due to its nutrient enrichment properties. Specific Background: Despite extensive research on various fertilizers, the specific effects of potassium humate on red cabbage (Ruby King cultivar) growth and yield, especially concerning the method of application, remain underexplored. Knowledge Gap: Limited studies have addressed the comparative impact of foliar spraying versus soil addition of potassium humate on cabbage vegetative growth and yield characteristics. Aims: This study aimed to evaluate the effects of different concentrations of potassium humate (0, 50, 100, 150 g.l-1) and application methods (foliar spraying and soil addition) on the growth and yield of red cabbage. Results: A randomized complete block design (RCBD) with three replications was implemented during the 2022-2023 agricultural season. Significant improvements in vegetative growth and yield were observed with the highest concentration (150 g.l-1) of foliar spraying. Key vegetative and yield parameters, such as plant height, stem length, number of leaves, leaf chlorophyll content, average head weight, and total yield, were positively influenced. Novelty: This study uniquely highlights the superior efficacy of foliar spraying with potassium humate at 150 g.l-1 over soil addition, providing insights into optimizing fertilization strategies for red cabbage. Implications: The findings advocate for the use of potassium humate, particularly via foliar spraying, as a beneficial organic fertilizer to enhance red cabbage growth and yield. This practice could lead to improved agricultural productivity and better tolerance of plants to environmental stresses, supporting sustainable agriculture initiatives. Highlights: Superior Growth: Foliar spraying with 150 g.l-1 potassium humate boosts growth. Yield Increase: Highest humate concentration yields maximum red cabbage. Effective Strategy: Foliar spraying outperforms soil addition for fertilization. Keywords: Potassium humate, foliar spraying, red cabbage, vegetative growth, yield enhancement